As caixas de Emília Nadal e outras caixas - Costa, Sara Antunes Prata Dias da, 1973- (2019)
The present work analyses the work of Emilia Nadal in what concerns her theme of ‘boxes’, mainly focusing on her work of the seventies. This work also seeks to reflect on the thematic of the ‘box’ in a much more comprehensive way, starting from an atlas of images. As a result, this work tryes to explore the extreme complexity of the “box” theme, relating it to the work of Emília Nadal, but also referring to the work of many other artists